Parameters indicating development of hypertension in three-year follow-up study of subjects with high normal blood pressure. (11th May 2022) - Kalos, T; Dimitriadis, K; Manta, E; Fragoulis, C; Konstantinidis, D; Tatakis, F; Leontsinis, I; Andrikou, I; Karioiri, M; Kouremeti, M; Drogaris, S; Polyzos, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: The clinical importance of a hypertensive response to exercise (HRE) in subjects with high normal blood pressure (BP) is not fully elucidated, while sympathetic overactivity followed by arterial stiffening are linked with development of hypertension (HTN). Purpose: The aim of this study was to assess the relation of HRE with sympathetic drive as assessed by muscle sympathetic nerve activity (MSNA) and arterial stiffness in subjects with high normal BP who developed hypertension in a 3 year follow up. Methods: 100 subjects with high normal office BP [systolic BP=130-139 mmHg and diastolic BP=85-89 mmHg] underwent a treadmill exercise stress test. Arterial stiffness was evaluated based on carotid to femoral pulse wave velocity (PWV). Sympathetic drive was assessed by MSNA levels. Follow up was every 6 months for 3 years, where BP was measured at both office (OffBP) and ambulatory blood pressure monitoring (ABPM). All participants offered lifestyle advises. Endpoint was development of HTN diagnosed either from OffBP or from ABPM. Then they were divided into Group I: those developed HTN and Group II: those remained normotensive. Results: Mean age 54±8 years, 42 males, baseline offBP: 132/82 mmHg, ABPM: 122/76 mmHg). Out of them, 50 subjects developed HRE (BP ³210mmHg in men and ³190 mmHg in women) and 40 HTN. Group I developed higher HRE (75% vs. 13%, p=0.026), higher levels of PWV (8.35 vs 7.5 m/sec, p=0.043) and MSNA levels (37 vs. 31 bursts, p=0.04), while did not differ at their metabolic profile. Echocardiographically left ventricular mass index did not differ statistically as E/A ratio of mitral valve inflow (0.92 vs 1.05, p=0.034). Those who developed HTN was related to night systolic BP from ABPM (116 vs 112 mmHg, p<0.04), as also to intermediate stage intervals of 3 min (160 vs 147 mmHg, p=0.068) and 6 min (181 vs 164, p=0.035) of Bruce protocol. A novel metric, the SBP/MET-slope [(peak SBP—resting SBP)/(peak MET-1)] found to add crucial information. Regarding those who developed HTN, SBP/MET-slope was higher in all stages till peak exercise (stage 1: 6.25 vs 4.25, stage 2: 7.6 vs 5.3, peak: 7.22 vs 5.1, p=0.035). It was noticed that they performed a higher exercise capacity (10 vs 11.5 METs) and additionally differ significantly in their maximal heart rate (HR) at peak exercise (154 vs 164, p=0.001). Conclusion: In subjects with high normal BP, a HRE, the intermediate BP intervals along with the SBP/MET-slope, identifies a state of systemic vascular resistance, arterial stiffening and sympathetic overdrive, as reflected by increased PWV and MSNA levels respectively. Additionally, exercise capacity demonstrates cardiovascular functional tolerance. These findings suggest that exercise testing provides determining clinical information regarding the overall cardiovascular status, proving its superior prognostic value as a hypertension screening tool, that alarms the physician to warn the patient to take action.